Employee engagement and open service innovation: The roles of creative self-efficacy and employee innovative behaviour - Wan, Xiaole; He, Ruixin; Zhang, Guixian; Zhou, Jian (Frontiers in Psychology, 2022)
Improving the innovation ability of organizations is the focal point of management study. This paper puts forward that innovative self-efficacy and employees’ innovative behaviour are continuous mediating variables, and discusses the influence mechanism of employees’ involvement and open service innovation from the individual factor level. In this study, a sample of 103 employees from travel companies was used to examine the hypothesis. The results show that employee engagement is positively related to open service innovation. Innovative self-efficacy plays a completely intermediary role between employee engagement and employee innovative behaviour; Creative self-efficacy and employees’ innovative behaviour play a continuous intermediary role between employees’ engagement and open service innovation. The results of this study will eventually help enterprises to carry out service innovation behaviour.